ICPi-Induced Graves' Disease with Pre-existing Autoimmune Thyroid Disorders: A Case Report and Literature Review - Wang, Xinpan; Chen, Doudou; Shi, Yun; Yang, Tao; Zheng, Xuqin (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2026)
BackgroundImmune Checkpoint Inhibitor (ICPi) therapy has revolutionized cancer treatment but can lead to immune-related adverse events (irAE), including thyroid dysfunction. The impact of ICPi on patients with pre-existing autoimmune thyroid diseases (PATD), particularly the development of Graves' disease, remains poorly understood.Case PresentationWe provide the first complete case of Graves' disease with ICPi therapy in a patient who already had Hashimoto's thyroiditis. The patient, a 52-year-old male, was diagnosed with lung adenocarcinoma and received Atezolizumab. Clinical evaluation revealed hyperthyroidism, confirmed by elevated thyroid hormones and autoantibodies (TRAb and TSAb). The patient was managed with methimazole and demonstrated a transient hyperthyroid phase followed by persistent hypothyroidism. Only 16 confirmed cases of Graves' disease induced by ICPi were reported. We conducted a review to investigate the clinical characteristics, risk factors, and prognosis trends associated with ICPi-induced Graves disease in PTAD patients. Additionally, changes in thyroid function and autoantibodies during and after ICPi treatment are examined.ConclusionThis case underscores the importance of monitoring thyroid function and autoantibodies in patients with PATD undergoing ICPi therapy. The findings suggest distinct differences in the humoral immune response between ICPi-induced and spontaneous Graves' disease, necessitating further research into autoantibody dynamics and their relationship with cellular immunity in these patients.
Keywords: autoantibody